The impact of the program by modifying certain nutritional behaviors accompanied by aerobic exercises on weight loss and improving some biological and physical measurements of women staying at home - بخوش , إبراهيم (Journal of Sport Science Technology and Physical Activities, 2024)
Through the study, we aim to identify the impact of a proposed program by modifying food behaviors with aerobic exercises for weight loss and improving some biological and physical measurements of women staying at home. The semi-experimental curriculum was used on a sample of 2 women staying at home. The sample was selected in the intended way. (Laboratory) and measurements (oceans) for achieving results, the most important results obtained were that the program for modifying dietary behaviors accompanied by aerobic exercises directly affected weight loss and improvement in physical and biological measurements .